Diagnosis of Lateral Ankle Ligament Injury in the Evaluation of Chronic Lateral Ankle Instability - Ji Young Jeon (The Korean Society of Radiology, 2021)
Chronic lateral ankle instability (CLAI) is a major complication of acute ankle sprain that can cause discomfort in both daily and sports activities and may lead to degenerative changes in the ankle joint as the long-term sequelae. The precise cause of CLAI remains debatable and is most probably multifactorial. However, identifying chronic lateral ankle ligament injury is critical in determining the primary etiology and formulating an appropriate treatment plan. This review discusses the features and effectiveness of various imaging techniques in diagnosing chronic lateral ankle ligament injury.